Citrus Diseases Exotic to Florida: Citrus Leprosis - Kuang Ren Chung; Ronald H. Brlansky (EDIS, 2006)
This document is one in a series designed to provide important information on the causal agent, symptoms, and transmission of exotic citrus diseases. Disseminating the information about the diseases to the citrus industry may prevent their introduction and spread in Florida. This document will focus on the exotic viral disease citrus leprosis. This document is PP148, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date April 2006.